Factors shaping giraffe behavior in U.S. zoos: A multi-institutional study to inform management - Jason D. Wark; Katherine A. Cronin (PLoS ONE, 2025)
Giraffes are one of the most commonly housed megafauna in zoos. Variation across zoos (e.g., geographic location, housing, and husbandry), may be expected to influence giraffe behavior. However, past studies have typically focused on a small number of zoos, limiting generalizable conclusions. Here, we expand upon a recent report on the behavior patterns of zoo-housed giraffes to evaluate the influence of several factors on giraffe behavior. Data were recorded on 66 individuals housed across 18 zoos over a one-year period (n = 8,330 10-min observation sessions). Generalized linear mixed models were used to analyze influences on the following behaviors: browsing, extractive foraging, other feeding, ruminating, oral stereotypies, inactive, and locomotion. Behaviors were first compared across outdoor and indoor housing conditions, then models were built for each behavior and housing condition to evaluate how multiple factors influenced behavior: organizational (habitat size, herd size, presence of public feeding opportunities); environmental (temperature, weather); temporal (time of day); and individual (age, sex). Behavioral differences between outdoor and indoor conditions were observed but were minimal. Overall, environmental and temporal factors influenced giraffe behavior the most, but all factors significantly influenced at least one behavior. Several findings are relevant for giraffe management. For example, giraffes living at zoos with public feeding opportunities spent less time browsing, more time in other feeding behaviors, and showed a trend of increased inactivity, suggesting these programs may negatively influence giraffe behavior. Oral stereotypies were negatively correlated with the time spent browsing or extractive foraging and temperature. This supports husbandry efforts to increase natural foraging behaviors in giraffes and highlights the need to better understand thermal comfort. The amount of outdoor space available was not associated with the time spent locomoting, countering common assumptions. Overall, these findings can begin to inform management decisions and guide additional investigations to identify specific, evidence-based husbandry recommendations.